Strategi Pengembangan Agroindustri Kopi Bubuk Berbasis Kelompok Wanita Tani di Pekon Padang Cahya Kecamatan Balik Bukit Kabupaten Lampung Barat - Erlina Rupaidah; Hernita Astuti (Inovasi Pembangunan : Jurnal Kelitbangan, 2015)
Coffe is an agricultural product that has some characteristics which is easily damaged, seasonal, a lot of variety so that need to process the coffee beans into semi-finished products like dried coffe beans and coffee powder in order to have high sales value. Some important issues that need to be discuss is raw materials availability, production process, marketing and other supporting aspects, so it’s necessary to identify all these aspects, which resulted in a decision that ground coffee agro-industry based woman farmer group at Padang Cahya Pekon can be developed after considering the results of the formulation of several subsystems. Subsystem needed is a subsystem of raw materials, operational subsystems, marketing subsystems and supporting subsystems. Government support is needed to help facilitate the training facilities for planning the development of the plantation bussines Tjap Tugu Liwa Coffe Brand, so as to ensure the availability of raw materials for the agro- production process by optimizing the role and function of women farmers which in turn can improve the welfare of the farmers